Wind Power Generation Based on Resonance Technology: توليد الطاقة الكهربائية من الرياح (Journal of Humanitarian and Applied Sciences, 2026)
This study investigates the generation of electrical power from wind energy using vortex-induced vibrations as an alternative to conventional rotating turbines. A nonlinear dynamic model was developed and implemented in MATLAB to simulate aerodynamic excitation and structural response over a wind speed range of 2 to 15 m/s.An analytical investigation was conducted to examine the effects of material type, column diameter (0.05–0.15 m), and wall thickness (2–6 mm) on resonance velocity and the resulting electrical power output. The results showed that carbon fiber reinforced polymer (CFRP) exhibited the highest critical resonance speeds (up to 12.4 m/s) and the maximum power output of approximately 48 W. Glass fiber reinforced polymer (GFRP) demonstrated moderate performance with a peak output of around 32 W, while high-density polyethylene (HDPE) resonated at lower wind speeds (3.1–5.6 m/s) but produced limited power output of about 10 W.Furthermore, increasing the column diameter enhanced power generation by up to 35%, whereas increasing wall thickness reduced vibration amplitude and decreased output efficiency by approximately 20%. These findings confirm the feasibility of resonance-based wind energy systems for small-scale urban applications.
Keywords: Wind Energy; Electricity Generation; Vortex-Induced Vibrations; Numerical Simulation; MATLAB; Composite Materials